ANALISIS IMPLEMENTASI DEEP LEARNING PADA KEMAMPUAN KOMUNIKASI SISWA SEKOLAH DASAR - Ikhsan, Wahyu Amirul; Heru Purnomo (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This research aims to analyze the implementation of the deep learning approach to developing elementary school students' communication skills, especially at SD Muhammadiyah Ambarbinangun. The main focus of this research includes the form of application of deep learning in the learning process, the learning activities used, student responses to the learning model, as well as the challenges and solutions faced by teachers. This research uses a qualitative method with a descriptive approach. Data collection was carried out through interviews and documentation. Data was collected from purposively selected sources and analyzed qualitatively to explore the deep meaning of the observed phenomena. The research results show that the application of deep learning through group discussions, presentations and project-based learning plays an important role in improving students' communication skills. Students become more active, confident and open in expressing opinions and working together in groups. Although time constraints were a major challenge, teachers managed to overcome this through continuous evaluation which included observations and written assessments. Overall, deep learning is proven to not only improve cognitive understanding, but also strengthen students' social and emotional aspects.